Interview with Cynthia Awuor from Care - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Cynthia Awuor from CARE on their collaboration with CCAFS. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya